Penentuan Penerima Beasiswa Prestatif Mahasiswa Menggunakan Metode Weighted Product di Lazis UNS - Azindani, Aziz; Yuly Saptomo, Wawan Laksito; Harsadi, Paulus (Fakultas Komputer Dan Desain, 2024)
The number of applicants of the student prestigious scholarship at LAZIS UNS exceeds the acceptance quota. The revenue quota is about 30 while the registrant reaches 200 people. This is due to one of them because of the high UKT which is now a college payment system. With the number of applicants LAZIS UNS must select 200 scholarship applicants in a fair and objective so that the scholarship recipient someday is a person who really has the achievement and need. Therefore an automated system is needed to assist LAZIS UNS in selecting 200 applicants to enter the fair and objective interview stage. The system is a decision support system for the determination of the prestigious scholarship recipient of LAZIS UNS students by using weighted product method (WP). Tests on the system that has been made to show positive results. The first test using black box testing, which test system that has been made per part in detail. Black box test results concluded the system works well. Then the second test using functional testing, that is comparing the calculations in the system with manual calculations using excel. Test results concluded calculation system with excel is same